The larvae of Altica koreana (Ogloblin) and A. viridicyanea (Baly) (Coleoptera: Chrysomelidae: Galerucinae: Alticini) - Hua, Yi; Ge, Si-Qin; Beutel, Rolf Georg; Zhang, Yong; Cui, Jun-Zhi; Yang, Xing-Ke (Zootaxa, 2013)
The first instar and mature larvae of Altica koreana (Ogloblin) and A. viridicyanea (Baly) are described and illustrated for the first time and compared with larvae of Altica caerulescens (Baly), A. cirsicola Ohno, and A. fragariae (Nakane). A key to the five related Altica species is also given.